Concepto del rendimiento académico en estudiantes universitarios - revisión narrativa. (2021)
Introduction: Although academic performance is one of the most important pillars in the development of an academic program, it presents risk factors that influence undergraduate students, therefore, the objective is to categorize the evidence regarding academic performance in health graduate schools from the point of view of their conceptual content and domains. Method: Scoping review that included 18 articles. Three scientific databases were consulted (PubMed, ScienceDirect and Google Scholar), the search was limited to the years from 2015 to 2020. Results: A variety of conceptual aspects and risk factors were found to be related to academic performance, of which the institutional factor was most marked. Conclusions: It is important to assess and integrate the concept of academic performance with the personal, institutional and social dimensions or factors, to guarantee a holistic evaluation of the graduate student in health sciences.